“It doesn’t matter at all—we are family”: Titling and joint property rights in Myanmar - Lambrecht, Isabel B.; Synt, Nang Lun Kham; Ei Win, Hnin; Mahrt, Kristi; Win, Khin Zin (Elsevier, 2024)
Many policy makers and academics striving for more gender equality consider joint property rights as preferable over sole rights, since the latter often discriminate against women. Several governments in low-, middle- and high-income countries have therefore imposed joint rights through modifications of statutory law or mandatory joint property registration. We first discuss a general theoretical framework of determinants of property rights with a focus on jointness and the interplay between statutory law, customary law and religious norms, as well as the importance of gendered customs, norms and perceptions around household, family and community arrangements. We then also relate this specifically to the case of Myanmar—based on literature and original qualitative data collected with men and women across all four agro-ecological zones in rural Myanmar. We find equal customary and statutory joint property rights regime upon marriage where inheritance rights are not different for men and women, but only one name is generally recorded on land use certificates. A strong sense of “togetherness”, including a custom of income pooling and rare occurrence of divorce, limits the rationale of marital partners to exercise rights solely rather than jointly. Nevertheless, which household members’ name is on a document is important for accessing credit or engaging with officials and government authorities, and strong patriarchal norms guide official and administrative procedures. Whereas short-term impacts of sole land titling seem limited, the extent to which sole or joint titling might affect gender equality in the longer term remains a topic of future research.